Inhibition of Rho-Associated Kinase Prevents Pathological Wound Healing and Neovascularization After Corneal Trauma. Issue 9 (September 2015) - Sijnave, Davine; Van Bergen, Tine; Castermans, Karolien; Kindt, Nele; Vandewalle, Evelien; Stassen, Jean-Marie; Moons, Lieve; Stalmans, Ingeborg
Abstract : Purpose: To investigate the effect of AMA0526, a specific inhibitor of rho-associated protein kinase (ROCK), on corneal neovascularization (NV) and scarring in different in vitro and in vivo experimental models. Methods: The effect of AMA0526 on cell viability, proliferation, and migration of human umbilical vein endothelial cells was determined. Its in vivo topical effect on NV was investigated in the corneal micropocket mouse model (bevacizumab as a control). The vessel length, clock hours, and NV area were measured on photographs. The effect of AMA0526 on pathological wound healing was investigated in the alkali burn mouse model (dexamethasone as a control). Corneas were scored for corneal opacity (CO) and NV after burn injury. Immunohistochemistry was performed to study inflammation, blood vessel density, and collagen III deposition after 7 days. Results: ROCK inhibition significantly inhibited vascular endothelial cell proliferation and migration in vitro in a dose-dependent manner. In the micropocket model, NV was significantly reduced by AMA0526 (37% reduction, P < 0.05) comparable to bevacizumab. CO and NV were reduced after AMA0526, compared with the vehicle ( P < 0.05 at all time points from day 3) after chemical burn. AMA0526 resulted in decreased inflammatory cell infiltration (26% reduction, P < 0.01), angiogenesis (47% reduction, P < 0.01), and collagen III deposition (27% reduction, P = 0.009) in the alkali burn model. AMA0526 administration showed results similar to those of dexamethasone with an additional antifibrotic effect. Conclusions: The ROCK inhibitor, AMA0526, efficiently inhibited angiogenesis in vitro, reduced CO and NV, and controlled the complete process of wound healing in vivo. These results warrant further investigation of the therapeutic potential of AMA0526 for corneal NV and scarring.